Membangun Parameter Intersubjektif Pornografi Dengan Perspektif Postmodernisme (Studi Kasus Putusan Nomor 39/Pid.Sus/2014/Pn.Wsb) - Sitompul, Josua (UI Scholars Hub, 2015)
One of fundamental idea established in postmodern concept is advoacy of diversity and freedom without determined by mainstreams. Postmodernism, though started from art and literature, has developed into various disciplines, include law. Discussions of the idea within legal discourses, at one side, have tried to link the mainstreams and the minorities in harmony, but at the other side, law demands to be exercised uniformly. This article discuss postmodern perspective in understanding pornography within the context of Law 44/2008 on Pornography; this law remains retain problems regarding the concept of pornography that law enforcement officers, particularly judges, have to solve. The question that the article seek to answer is how the concept of postmodernism can help judges to establish parameter that is rational and intersubjective to determine pornography content. One case regarding pornography related to metal music is raised as an example.